#### Answer

x=-9

#### Work Step by Step

Simplifying
27 + 5x = 9 + 3x
Solving
27 + 5x = 9 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
27 + 5x + -3x = 9 + 3x + -3x
Combine like terms: 5x + -3x = 2x
27 + 2x = 9 + 3x + -3x
Combine like terms: 3x + -3x = 0
27 + 2x = 9 + 0
27 + 2x = 9
Add '-27' to each side of the equation.
27 + -27 + 2x = 9 + -27
Combine like terms: 27 + -27 = 0
0 + 2x = 9 + -27
2x = 9 + -27
Combine like terms: 9 + -27 = -18
2x = -18
Divide each side by '2'.
x = -9
Simplifying
x = -9